2018
DOI: 10.17645/up.v3i1.1231
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Emotional Responses of Individuals to Urban Green Space Using Twitter Data: A Critical Comparison of Three Different Methods of Sentiment Analysis

Abstract: In urban research, Twitter data have the potential to provide additional information about urban citizens, their activities, mobility patterns and emotion. Extracting the sentiment present in tweets is increasingly recognised as a valuable approach to gathering information on the mood, opinion and emotional responses of individuals in a variety of contexts. This article evaluates the potential of deriving emotional responses of individuals while they experience and interact with urban green space. A corpus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…By their simultaneous use, together the 5 characteristics of the Smart-Natural city interface have the potential to help start dialogues to resolve concerns (Arts et al, 2015;Roberts, 2017) over how these benefits are transferred to and received by urban populations and the circumstances under which this can happen most effectively. The use of this new approach can guard against widening the digital divide and amplifying poverty gaps as described by Hernandez & Roberts (2018), allows us to 'see the expertise of citizens' (Noveck, 2015) and so address the disconnect challenge identified by Colding & Barthel (2017).…”
Section: Discussion -The Value and Opportunity Of The Smart City -Natmentioning
confidence: 99%
See 1 more Smart Citation
“…By their simultaneous use, together the 5 characteristics of the Smart-Natural city interface have the potential to help start dialogues to resolve concerns (Arts et al, 2015;Roberts, 2017) over how these benefits are transferred to and received by urban populations and the circumstances under which this can happen most effectively. The use of this new approach can guard against widening the digital divide and amplifying poverty gaps as described by Hernandez & Roberts (2018), allows us to 'see the expertise of citizens' (Noveck, 2015) and so address the disconnect challenge identified by Colding & Barthel (2017).…”
Section: Discussion -The Value and Opportunity Of The Smart City -Natmentioning
confidence: 99%
“…New digital techniques for informing better decisions are not yet systemic but are emerging and Arts et al 2015have identified a number of categories of data alongside risks and problems that accompany digital conservation. Others have identified specific applications for urban landscapes, remote and human sensing (see for example; Blaschke et al, 2011;Hill, 2016;IWUN, 2017;Roberts et al, 2018;Seresinhe et al, 2017 andTu et al, 2018). Carton & Ache (2017) have specifically explored the rise of citizen-sensor-networks, combining civic engagement and ICT.…”
Section: Integrating Smart and Natural City Discourses?mentioning
confidence: 99%
“…Many applications use the output of latent semantic analysis (LSA) from a-typically online-text corpus and utilize semantic, semiotic, and linguistic analysis (e.g., [91][92][93][94]). In fact, those methods are increasingly used to gather information on the mood, opinion, and emotional responses of individuals in a variety of contexts, namely space, time, and situation-specific (only applicable for this situation) context (e.g., [77,95,96]). Various recent studies using social media, particularly Twitter data, aim to reveal a sense of place.…”
Section: Place Names/place Modelingmentioning
confidence: 99%
“…Various recent studies using social media, particularly Twitter data, aim to reveal a sense of place. While many computer scientists and computer linguists, on the other hand, discover the power of spatial concepts [95,[97][98][99][100][101][102][103], and likewise, GIScientists discover the potential of semantic analyses [77,94,96,[104][105][106], the dividing line between spatial and non-spatial applications diminishes.…”
Section: Place Names/place Modelingmentioning
confidence: 99%
“…Twitter data are used for assessing various events (D'Andrea et al, 2015;Gu et al, 2016;He, Boas, Mol, & Lu, 2017;Purohit et al, 2014;Qian, 2016;Roberts et al, 2018;Tang et al, 2017) including natural disasters, mass emergency, acts of terrorism, extreme weather events, political protests, and transportation events. In a study conducted by Mirończuk and Protasiewicz (2018), the authors have reviewed recent research to understand the general approach of text classification practices and identify the future research questions related to text classification (Mirończuk & Protasiewicz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%